Headmasters Training for Creating the In-School Quality Management System - M. A. Desyateritchenko (Russian State Vocational Pedagogical University, 2015)
The paper looks at the issue of the further professional training of educational staff for developing quality management systems. Mastering the qualitative educational practices provides the effective school training quality assessment, as well as optimization of staff, material, technical and financial resources, and consideration of the requirements of educational process participants. The peculiarities of the quality management penetration into the general educational sphere are analyzed. The factors obstructing the innovative experience spreading are denoted along with the corresponding ways of experimental practices. The content and organizational technological aspects of headmasters and teaching staff readiness for implementing the above innovation in the system of further professional training are defined. The stages of a lyceum readiness for certification of in-school quality management system according to the international standard ISO 9001:2008 are described. The author points out the necessity of developing the training system for managerial and teaching staff with regard to the person oriented and humanity approach.